The impact of university freshmen’s mental health on academic performance: an empirical study based on M University in Fujian Province, China - Deng, Xue; Li, Cheng (Frontiers in Public Health, 2024)
ObjectiveTo investigate the impact of freshmen’s mental health on their short-and long-term academic performance, as well as to provide empirical evidence for improving university students’ mental health intervention tactics and higher education quality.MethodsA multiple regression model was used to analyze student data from 3 years of enrollment at M University in Fujian Province.ResultsDifferent mental health problems have a significant impact on academic performance, which varies by gender, enrollment year, and subject. Somatization, anxiety, and depression have a significant negative impact on both comprehensive and single-subject scores, while anxiety, social aggression, and other variables can increase academic performance in certain settings. Some effects are notably moderated by gender and enrollment year.ConclusionUniversity officials should strengthen mental health surveillance and intervention during the first few years of student enrollment to mitigate the harmful impact of mental health issues on academic performance. The moderate to strong effect sizes for variables like somatization, depression, and anxiety indicate that early interventions could be crucial in reducing their negative impact on both short-and long-term academic outcomes. Furthermore, the study discovered disparities in mental health and academic performance across students of different genders and enrollment years, emphasizing that educational personnel should design more tailored mental health support methods that consider these differences.